"A ciência e a verdade": a psicanálise proposta como uma ciência no texto de Jacques Lacan - Grostein, Sandra Arruda (2010)
The following research aims to find in the text Science and Truth, by Jacques Lacan, published in 1966, the arguments with which he justifies the scientific vocation of psychoanalysis and most importantly, shows that it is located in the field of science through the subject. Searching beyond this, to analyze if these justifications are consistent and to identify through which elements they are supported. The investigation is divided into three parts, which correspond to the three chapters of the dissertation, which have the following focus: The subject of science, the object of psychoanalysis and the scientific vocation of psychoanalysis. To bring together science and psychoanalysis, Lacan, in the main text, refuses to include psychoanalysis in the area of human science. Considering this, the research aims to find, through the study of the criticism completed by Lacan, of man as the subject of science, the debate with psychology, implicit in the text. The argument that there is equality between the subject of science and the Freudian unconscious is another focus of this research. Searching to identify the consistency of this argument through the Freudian references that Lacan is examining in the main text. Concluding that psychoanalysis had, and still has, as in Lacan s view, to face two big challenges to be included in the scientific field: the first has to do with the question of the object and the second deals with the differentiation between psychoanalyses and psychology, that the latter seeks to include the first in its set, since it claims for a unity in its field of knowledge